Subcritical ethanol extraction of flavonoids from Moringa oleifera leaf and evaluation of antioxidant activity. (1st March 2017) - Wang, Yongqiang; Gao, Yujie; Ding, Hui; Liu, Shejiang; Han, Xu; Gui, Jianzhou; Liu, Dan
Highlights: A large scale subcritical ethanol extraction was conducted to extract flavonoids. An optimal condition of extraction was proposed. The extraction process was energy-saving. The extracts showed strong antioxidant ability. HPLC–MS analysis was performed to identify the flavonoids. Abstract: A large-scale process to extract flavonoids from Moringa oleifera leaf by subcritical ethanol was developed and HPLC–MS analysis was conducted to qualitatively identify the compounds in the extracts. To optimize the effects of process parameters on the yield of flavonoids, a Box-Behnken design combined with response surface methodology was conducted in the present work. The results indicated that the highest extraction yield of flavonoids by subcritical ethanol extraction could reach 2.60% using 70% ethanol at 126.6 °C for 2.05 h extraction. Under the optimized conditions, flavonoids yield was substantially improved by 26.7% compared with the traditional ethanol reflux method while the extraction time was only 2 h, and obvious energy saving was observed. FRAP and DPPH assays showed that the extracts had strong antioxidant and free radical scavenging activities.